ANALYSIS OF FAMILY SUPPORT TEAM PERFORMANCE STRENGTHENING IN EFFORTS TO REDUCE THE INCIDENT OF STUNTING IN WEST SUMATRA PROVINCE IN 2025 - Hariani, Santi; Datin Hafizah Che Hassan; Das, Sreemoy Kanti (JCI Publisher, 2025)
The Family Support Team is a group of support staff in the sub-district/village/nagari consisting of Midwives, PKK Team Cadres and KB Cadres in providing support to prospective brides/prospective fertile couples, pregnant women, postpartum mothers, and children aged 0-59 months, providing counseling, facilitating referral services, receiving social assistance and surveillance of families at risk of stunting. Stunting is a growth and development disorder characterized by a child's height that is not appropriate for their age. This study aims to analyze the performance of the family support team in an effort to reduce the incidence of stunting and the factors that influence the performance of the family support team. This study uses a qualitative method using a purposive sampling technique with 38 informants, through interviews, focus group discussions, observations and document reviews. The results of the study revealed that the indicators of the quality and quantity of TPK work in West Sumatra Province that were not in accordance with expectations were neatness, success capability, speed, work results, facilities and infrastructure and coordination between agencies where reports were not in accordance with the existing family system data in the BKKBN application caused by the lack of TPK knowledge in using the elsimil application and four indicators of the national sensitive intervention program were not achieved from the predetermined targets and the increase in stunting cases. Factors that influence TPK performance are the support and commitment of the government and the community, the existence of programs that have a direct impact on the community and, socialization that changes community behavior to care about stunting prevention programs, strengthening the competence of TPK cadres, strengthening convergence and multi-stakeholder involvement, integrated monitoring and evaluation and utilization of stunting risk family data in handling stunting cases.